Construcción del imaginario y cultura migratoria entre los bolivianos en Argentina (2022)
Among all migrations in Latin America, those from Bolivia to Argentina represent a considerable and persistent social phenomenon for both countries. Bolivians’ predilection for Argentina reveals a “time-honoured story” taking shape through spatial logics, transnational dynamics and specific symbolic contents. The work aims to reconstruct the evolution of this story of exchange among social bodies over time, to explore the relationship between migratory tradition, work dimension and family life cycle, spatial and transnational dynamics, and the continuity/change relation with respect to both the gender dimension and the imaginary and social representations of and on migrants.